Polarization of Lyman-α emission in proton-hydrogen collisions studied using a semiclassical two-center convergent close-coupling approach - Avazbaev, S.; Kadyrov, Alisher; Abdurakhmanov, Ilkhom; Fursa, Dmitry; Bray, Igor (American Physical Society, 2016)
© 2016 American Physical Society. The semiclassical convergent close-coupling approach to ion-atom collisions has been extended to include electron-transfer channels. The approach has been applied to study the excitation and the electron-capture processes in proton-hydrogen collisions. The integral alignment parameter A20 for polarization of Lyman-α emission and the cross sections for excitation and electron-capture into the lowest excited states have been calculated for a wide range of the proton impact energies from 1 keV to 1 MeV. The results are in good agreement with experimental measurements.